Mechanical properties and metallographic analysis of plasma spray APS - Ni5.5wt.%Al5wt.%Mo coatings - Mrdak, Mihailo R. (Vojnotehnički glasnik / Military Technical Courier, 2019)
This paper presents the testing of the mechanical and microstructural characteristics of atmospheric plasma spray (APS) coatings of Ni5.5wt.%Al5wt.%Mo composite powder. The aim of this study was to optimize powder feed (g/min) in order to deposit  NiAlMo coating layers with optimum mechanical and structural characteristics to worn aviation parts made of Ni alloy exposed to a combination of corrosion and wear. The microhardness of the deposited layers was tested using HV0.3 and tensile bond strength was tested by tensile testing. The morphology of powder particles was examined on a SEM (scanning electron microscope). The NiAlMo coating microstructure was examined on an optical microscope (OM). Fracture morphology of the top layer was tested on an electronic scanning microscope (SEM). It was found that the control of powder feed can result in coatings with good bond strength.
Keywords: atmospheric plasma spraying (APS); microstructure; Ni5.5wt.%Al5wt.%Mo; microhardness; bond strength